Effect of coffee consumption on the risk of gastric cancer: a systematic review and meta-analysis of prospective cohort studies. - Haibin Liu; Ying Hua; Xiangyun Zheng; Zhaojun Shen; Hui Luo; Xuejiao Tao; Zhiyi Wang (PLoS ONE)
Background and objectives Results from observational epidemiologic studies on the relationship between coffee consumption and gastric cancer are inconsistent and inconclusive. To assess the association between coffee consumption and the risk of gastric cancer, we summarized evidence from prospective cohort studies. Methods Relevant studies were retrieved through computer searches (PubMed, EmBase and the Cochrane Library) and a review of references up to December 2014. The quality of the included studies was evaluated by Newcastle-Ottawa quality assessment scale. We used a meta-analytic approach to estimate overall hazard ratios (HRs) and 95% confidence intervals (CIs) for regular coffee drinkers versus individuals who seldom drank coffee. Sensitivity analysis and subgroup analysis were performed to assess the reliability of our results. A dose-response analysis was performed to assess the risk of gastric cancer based on the level of coffee consumption. Results Nine prospective cohort studies involving 1,250,825 participants and 3027 gastric cancer cases were included in this meta-analysis. The pooled HR of gastric cancer for the study-specific regularly versus seldom coffee drinking categories was 1.05 (95% CI, 0.88 to 1.25) with significant heterogeneity across studies (I(2) = 74.0%, P = 0.000). After the sensitivity analysis, three studies were deleted; however the association remained insignificant (HR, 0.99; 95% CI, 0.91 to 1.08). Subgroup analysis by anatomic location showed a risk for coffee consumption associated with cardia cancer (HR, 1.23; 95% CI, 1.04 to 1.45; heterogeneity, I(2) = 36.4, P = 0.207). In the dose-response analysis, there was no significant association between coffee intake (in cups) and the risk of gastric cancer (P for linearity trend and non-linearity > 0.05). Conclusion Our meta-analysis demonstrated that coffee consumption was not associated with overall gastric cancer risk; however, coffee consumption may be a risk factor for gastric cardia cancer.